Benchmarking bipedal locomotion: a unified scheme for humanoids, wearable robots, and humans - Torricelli, Diego; Gonzalez Vargas, Jose Angel; Veneman, Jan F.; Mombaur, Katja; Tsagarakis, Nikos; Del-Ama, Antonio J.; Gil-Agudo, Angel; Moreno, Juan C.; Pons, Jose L. (IEEE robotics & automation magazine, 2015)
In the field of robotics, there is a growing awareness of the importance of benchmarking [1], [2]. Benchmarking not only allows the assessment and comparison of the performance of different technologies but also defines and supports the standardization and regulation processes during their introduction to the market. Its importance has been recently emphasized by the adoption of the technology readiness levels (TRLs) in the Horizon 2020 information and communication technologies by the European Union as an important guideline to assess when a technology can shift from one TRL to the other. The objective of this article is to define the basis of a benchmarking scheme for the assessment of bipedal locomotion that could be applied and shared across different research communities.
Gesehen am 06.07.2020